Modelling and Analysis of Custom Power Device for Improve Power Quality - Gurrala Madhusudhan Rao (International Journal of Electrical and Computer Engineering (IJECE), 2011)
Abstract: This paper describes the model and analyzes custom power devices for compensating voltage sag and swell conditions in three phase systems. Faults occurring in power distribution systems or facilities in plants cause the voltage sag or swell. If a fault occurs, it can damage the power system or user’s facility. Sensitivity to voltage sags and swells varies within different applications. For sensitive loads (PLC’s, paper mills etc.), even voltage sags of short duration can cause serious problems in the entire system. Normally, a voltage interruption triggers a protection device, which causes shutdown of the entire system. In order to mitigate power interruptions, this paper proposes a scheme for voltage sag support based on a pulse width modulated autotransformer. The proposed scheme is able to quickly recognize the voltage sag or swell condition, and it can correct the voltage by either boosting the input voltage during voltage sag events or reducing the voltage during swell events.DOI:http://dx.doi.org/10.11591/ijece.v1i1.41